HUBUNGAN DAYA TAHAN DAN KECEPATAN TERHADAP HASIL LARI 800 METER PUTRA ATLET ATLETIK SMA NEGERI OLAHRAGA PROVINSI RIAU - Tomi Lukman Hakim. P; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observation of researchers conducted at the athletic State High school athletics athletes, there are still many problems especially on the number of the 800-Meter-long running distance that can be seen as in the national match, in the game the athlete has been good but has not reached the peak achievement. The purpose of this research is to know the durability and speed relationship with the results of the 800 Meter men's run on athletic athletes high school sports in Riau province. The population in this study was the athletic athlete of the 800 Meter Sprint High School of Riau province which numbered as much as 6 people. Sample withdrawal using the total sampling technique.This research instrument bleep test for measuring Vo2 Max, running 30 meters to measure speed and running 800 meters. The collected Data will be analyzed using double correlation. Based on the results of the research that the author has outlined in the previous chapter, it can be taken the conclusion as follows. From the results obtained durability there is no significant relationship with the results of running 800 meters in athletic athletes SMA State sports Riau Province, with rcount = 0.028 < Rtable = 0.950. If compared with the interpretation of correlation, there is a very low relationship that ranges from 0.00-0,199. From the results obtained speed there is no significant relationship with the results of running 800 meters in athletic athletes SMA State sports Riau Province, with rcount = 0.395 < Rtable = 0.950. If compared with the interpretation of correlation, there is a low relationship that ranges from 0.20-0,399. There was no significant relationship between the durability and speed of the 800 meter run in athletic high school sports athletes in Riau province, with rcount = 0.533 < Rtable = 0.950. If compared with the interpretation of correlation, there is a moderate relationship ranging from 0.40-0,599.Key Words: Endurance, Speed, Running Results 800 Meters